2015
DOI: 10.1159/000369701
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Fine Particulate Matter Induces Apoptosis of Endothelial Progenitor Cells Through Reactive Oxygen Species Formation

Abstract: Background/Aims: Bone marrow (BM)-derived endothelial progenitor cells (EPCs) play a critical role in angiogenesis and vascular repair. Some environmental insults, like fine particulate matter (PM) exposure, significantly impair cardiovascular functions. However, the mechanisms for PM-induced adverse effects on cardiovascular system remain largely unknown. The present research was to study the detrimental effects of PM on EPCs and explore the potential mechanisms. Methods: PM was intranasal-distilled into male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 49 publications
(61 reference statements)
8
62
0
Order By: Relevance
“…This was in tandem with our current gene expression analysis, which showed increased expression of inflammatory cytokines namely TNF-α and IL-6 following exposure to both PM2.5 and PM10. These results are in agreement with a previously reported studies in which PM2.5-10 increased the expression levels of the inflammatory markers including TNF-α and IL-1β in endothelial progenitor cells [37], IL-6 and IL-8 in monocytes [38], IL-6 in Kupffer cells [39] and TNF-α, IL-6 and IL-8 in lung epithelial cells [40]. The mechanism through which the airborne particulates induced apoptosis and increased the expression level of the inflammatory markers was attributed to triggering the formation of the reactive oxygen species (ROS) [37,40,41].…”
Section: Discussionsupporting
confidence: 94%
“…This was in tandem with our current gene expression analysis, which showed increased expression of inflammatory cytokines namely TNF-α and IL-6 following exposure to both PM2.5 and PM10. These results are in agreement with a previously reported studies in which PM2.5-10 increased the expression levels of the inflammatory markers including TNF-α and IL-1β in endothelial progenitor cells [37], IL-6 and IL-8 in monocytes [38], IL-6 in Kupffer cells [39] and TNF-α, IL-6 and IL-8 in lung epithelial cells [40]. The mechanism through which the airborne particulates induced apoptosis and increased the expression level of the inflammatory markers was attributed to triggering the formation of the reactive oxygen species (ROS) [37,40,41].…”
Section: Discussionsupporting
confidence: 94%
“…* placebo treatment vs healthy control, P<0.05, n=5; ** probucol treatment vs healthy control, p<0.05, n=5; # probucol treatment vs placebo, p<0.05, n=5. stress were involved in EPC dysfunction in many diseases including hyperlipidemia, diabetes, coronary artery disease, renal ischemia-reperfusion injury and air pollution related cardiovascular disease [64][65][66][67]. Our data showed that ox-LDL was able to increase both BM and blood extracellular and blood intracellular ROS levels in mouse with ox-LDL treatment.…”
Section: Discussionmentioning
confidence: 74%
“…It is consistent with our previous study of renal tubular epithelial cells [11] in which high glucose stimulation caused an immediate increase in the association of HMGB1 with TLR4, and this effect of high glucose was dependent on ROS production. ROS are generated by a variety of stimuli and act as a signaling molecule [30,31], and our data suggest that HMGB1-TLR4 axis could be a common downstream signal of ROS.…”
Section: Discussionmentioning
confidence: 87%